Shokugeki no Soma Anime as a Form of Japanese Soft Power in Indonesia - Gayatri, Gita Dewi; Konety, Neneng (Padjadjaran Journal of International Relations, 2026)
Anime is a Japanese popular culture that has gone global. The Shokugeki no Soma anime is one of the anime that has many fans in various countries, one of which is in Indonesia. Although this anime has never been broadcast on Indonesian television stations, Ani-One Asia, a business branch of Medialink Group engaged in content distribution and brand licensing, has broadcast the Shokugeki no Soma anime with Indonesian subtitles on the YouTube platform for free. This study aims to explain the Shokugeki no Soma anime as a form of Japanese soft power in Indonesia. This study uses a qualitative method with interpretive analysis. The object of study is the Shokugeki no Soma anime which displays scenes containing Japanese cultural elements. Data collection was carried out through interviews and literature studies. In analyzing, the researcher used the theory of soft power and cultural diplomacy. From the results of the study, the researcher found that the Shokugeki no Soma anime is a product of Japanese popular culture that is used as a source of soft power. The Washoku and Onsen cultures featured in the Shokugeki no Soma anime are Japan's efforts to attract the interest of its viewers so that they want to know more about Japan. Apart from contributing as a soft power instrument that introduces Japanese culture, the Shokugeki no Soma anime also contributes as a tool for Japanese cultural diplomacy in the tourism sector because it can influence viewers to go to Japan because they want to experience Washoku and Onsen culture directlyAnime merupakan budaya populer Jepang yang telah mendunia. Anime Shokugeki no Soma adalah salah satu anime yang memiliki banyak penggemar di berbagai negara, salah satunya di Indonesia. Meski anime ini belum pernah tayang di stasiun televisi Indonesia, tapi Ani-One Asia, cabang bisnis dari Medialink Group yang bergerak di bidang distribusi konten dan lisensi merek telah menayangkan anime Shokugeki no Soma dengan takarir Bahasa Indonesia di platform YouTube secara gratis. Penelitian ini bertujuan untuk menjelaskan tentang anime Shokugeki no Soma sebagai bentuk soft power Jepang di Indonesia. Penelitian ini menggunakan metode kualitatif dengan analisis interpretatif. Objek yang diteliti adalah anime Shokugeki no Soma yang menampilkan adegan-adegan berisi elemen budaya Jepang. Pengumpulan data dilakukan melalui wawancara dan studi pustaka. Dalam menganalisis, peneliti menggunakan teori soft power dan diplomasi budaya. Dari hasil penelitian, peneliti menemukan bahwa anime Shokugeki no Soma merupakan produk budaya populer Jepang yang dimanfaatkan sebagai sumber soft power. Budaya Washoku dan Onsen yang ditampilkan dalam anime Shokugeki no Soma merupakan upaya Jepang untuk menarik minta para penontonnya agar mereka ingin tahu lebih dalam tentang Jepang. Selain berkontribusi sebagai instrumen soft power yang memperkenalkan budaya Jepang, anime Shokugeki no Soma juga berkontribusi sebagai alat diplomasi budaya Jepang dalam sektor pariwisata karena dapat mempengaruhi para penontonnya untuk pergi ke Jepang sebab mereka ingin merasakan secara langsung budaya Washoku dan Onsen